4CPS-196 Impact of clinical pharmacist interventions made in the presence of electronic prescription. (March 2019) - Alcobia, A; Santos, A; Simões, A
Abstract : Background: One of the roles of the clinical pharmacist is to review medical prescriptions and suggest therapeutic interventions to avoid potential adverse events in hospitalised patients. Purpose: To analyse the pharmaceutical interventions (PI) during electronic prescription validation and the degree of acceptance. Material and methods: Retrospective study in a four-week period, using the electronic prescription order entry to quantify and classify PI, and the acceptance rate by the prescribers. The PI was classified as Informative: pharmaceutical compounding (PC), therapeutic equivalent (TE) and drug availability (DA), and Safety: dose modification (DM), posology adjustment (PA), pharmacokinetics monitoring (PM), drug combination (DC), dose duplicity (DD), incorrect dosage (ID), renal dose adjustment (RDA), therapeutic recomendation (TR) and administration (A). Results: During this period there were a total of 143 PI in 95 patients, 60% Informative (DA 33.6%, TE 17.5% and PC 11.9%) and 40% Safety-related (PA 15.4%, PM 9.8%, TR 2.8%, DD 2.8%, DM 2.1%, RDA 1.4%, A 1.4%, DC 0.7% and ID 0.7%). The rate of acceptance was 84.6%. The PI made by phone, email or handwritten were not accounted for in this analysis but are undoubtedly an important part of the pharmacist interventions since this type of electronic advice is only available on the prescription menu. Conclusion: The acceptance rate of PIs was highly significant, which demonstrates that physicians take into account these recomendations. PI registration is essential in emphasising the role of the pharmacist in preventing medication errors and improving patient safety. References and/or acknowledgements: Romero G. Intervenciones farmaceuticas, errores de medicación y su gravdad en el área de observación de un hospital de tercer nível. Rev Ofil Ila Phar 2018;28:115–21. Sartore M. The significance of pharmacy interventions: and updated review in the presence of electronic order entry. AM J Pharm Ben 2014;6:e24–e30. Available at Internet https://www.ajmc.com/journals/issue/2014/ajpb_marapr2014/the-significance-of-pharmacy-interventions-an-updated-review-in-the-presence-of-electronic-order-entry No conflict of interest.